A new hairy Leptogium (section Mallotium) from Rio Grande do Sul State, Brazil - Kitaura, Marcos Junji [UNESP]; Käffer, Márcia Isabel; Marcelli, Marcelo Pinto; Martins, Suzana Maria De Azevedo (Instituto de Botânica, 2014)
The hairs of Leptogium species are complex structures which determine taxonomic groups within the section Mallotium. The hairs composed of cylindrical cells can be short and, when present on the surface, give origin to glass-or velvet-like hairs. Leptogium involutum, collected in Southern Brazil, a new species with velvet-like hairs is described herewith.

Os pêlos das espécies de Leptogium são estruturas complexas que podem determinar grupos dentro da seção Mallotium. Os pêlos compostos de células cilíndricas podem ser curtos e, quando presentes oferecem a superfície uma aparência brilhante (como vidro) ou aveludada. Leptogium involutum, coletada na região Sul do Brasil, uma espécie nova com pêlos aveludados é descrita aqui.
Uma nova espécie de Leptogium com pêlos (seção Mallotium) do Estado do Rio Grande do Sul, Brasil
Keywords: células cilíndricas; Leptogium velutinum; margem involuta; cylindrical cells; involute margin; Leptogium velutinum